2023
DOI: 10.21009/jtp.v25i2.27433
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Flipped Classroom on Students' Mathematics Abilities: Effectiveness and Heterogeneity Analysis

Endang Sulistyowati,
Julham Hukom Jul,
Ali Muhtadi

Abstract: Despite numerous studies investigating whether the Flipped Classroom method is more effective in enhancing students' mathematical abilities compared to conventional teaching methods, previous research has shown inconsistent results. This study aims to examine the effectiveness of the Flipped Classroom method on students' mathematical abilities compared to conventional methods and to investigate the factors that can influence the effectiveness of using the Flipped Classroom method on students' mathematical abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
2
1
0
2
Order By: Relevance
“…The FC model proved to be the most effective in using the Moodle platform, followed by Edmodo, Khan Academy, WhatsApp, and Google Classroom. This finding is in line with the meta-analysis conducted by Sulistyowati et al (2023), who found that the platform approach to using the flipped classroom model can provide different mathematics learning outcomes. Therefore, it is important for mathematics educators to pay attention to the right approach when practicing the flipped classroom model.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The FC model proved to be the most effective in using the Moodle platform, followed by Edmodo, Khan Academy, WhatsApp, and Google Classroom. This finding is in line with the meta-analysis conducted by Sulistyowati et al (2023), who found that the platform approach to using the flipped classroom model can provide different mathematics learning outcomes. Therefore, it is important for mathematics educators to pay attention to the right approach when practicing the flipped classroom model.…”
Section: Discussionsupporting
confidence: 88%
“…The FC model was found to be most effective in the type of FC model integrated with GeoGebra (FC-G), followed by FC integration with game-based learning (FC-GbL), FC integration with cultural learning (FC-CL), FC integration with PBL (FC -PBL), and finally conventional FC. The meta-analysis by Purnomo et al (2022) and Sulistyowati et al (2023) aligns with this finding, indicating that varying learning approaches in the flipped classroom model can lead to varying mathematics performance. Therefore, it is important for mathematics educators to pay attention to appropriate learning approaches when practicing the flipped classroom model.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Siswa memiliki waktu belajar yang maksimal untuk menyelesaikan masalah yang kompleks, berkolaborasi dengan sesama, dan menjelaskan pemikiran mereka dengan lebih mendalam (Palinussa et al, 2021). Melalui aktivitas-aktivitas seperti diskusi kelompok, eksperimen, dan proyek, flipped classroom merangsang pemikiran analitis dan kreatif siswa, memungkinkan mereka untuk mengembangkan pemahaman yang lebih mendalam tentang konsep-konsep matematika dan menerapkan pengetahuan tersebut dalam situasi dunia nyata (Purnomo et al, 2022;Sulistyowati et al, 2023).…”
Section: Pendahuluanunclassified
“…Penelitian meta-analisis sebelumnya telah secara luas menginvestigasi dampak penerapan flipped classroom dalam konteks pembelajaran matematika (Güler et al, 2023;Purnomo et al, 2023;Sulistyowati et al, 2023;. Namun, meskipun banyak penelitian telah dilakukan, fokus utama belum secara khusus ditujukan untuk mengevaluasi hasil High Order Thinking Skills (HOTS) matematika melalui intervensi model flipped classroom.…”
Section: Pendahuluanunclassified